Analisis Faktor-Faktor yang Mempengaruhi Kecemasan Pada Pasien Ca Mammae yang Sedang Melakukan Tindakan Kemoterapi - Ruslany, Christina; Fauzi, Tengku Muhammad; Damanik, Irene (Universitas Methodist Indonesia, 2019)
Background : Breast cancer is the most commonly diagnosed cancer in women and is also the leading cause of death in women worldwide. With about 1.3 million new cases and an estimated 458,000 deaths reported in 2008. Types of therapy that can be used in the treatment of cancer include surgery, radiation, and chemotherapy and hormonal therapy. Chemotherapy can affect cell health as well as cancer cells, leading to side effects that are common with medications. Psychological side effects in patients with chemotherapy are fear, anxiety to panic. The purpose of this study was to determine the relationship between the factors that influence the anxiety of Ca Mammae patients with chemotherapy. Methods : The research method used was a Literature Review, using secondary data. Data were collected using documentation techniques. The research journals used were 7 journals with inclusion criteria for the publication date of the last 5 years, the language used was Indonesian or English, with the subject of the study of patients with a diagnosis of Ca mammae, and full text publication. Conclusion : There is a relationship between the factors that influence anxiety in breast cancer patients undergoing chemotherapy. Starting from the factors of age, occupation, education, stage of cancer, and the frequency of chemotherapy.